Maintenance process planning in the era of industry 4.0 – Proknow–C method - Silva, Natália Aragão; Servare Junior, Marcos Wagner Jesus (Brazilian Journal of Production Engineering, 2022)
The purpose of this article is to present the use of the scientific study method ProKnow - c, which consists of the selection and composition of a bibliographic portfolio, which aims to direct and optimize the search for articles considered relevant, according to the researched topic. This method consists of 3 steps: portfolio selection, bibliometric analysis and systemic analysis. In the course of this article, this analysis will be exposed, which made it possible, through filters, to select 10 scientific articles that were directed to the theme: Planning the maintenance process in the era of industry 4.0.